2017
DOI: 10.1080/17470218.2016.1181768
|View full text |Cite
|
Sign up to set email alerts
|

The multisensory basis of the self: From body to identity to others

Abstract: By grounding the self in the body, experimental psychology has taken the body as the starting point for a science of the self. One fundamental dimension of the bodily self is the sense of body ownership that refers to the special perceptual status of one’s own body, the feeling that “my body” belongs to me. The primary aim of this review article is to highlight recent advances in the study of body ownership and our understanding of the underlying neurocognitive processes in three ways. I first consider how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
309
2
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(359 citation statements)
references
References 80 publications
(133 reference statements)
10
309
2
9
Order By: Relevance
“…Second, a profound admiration for amputees up to a sexual attraction towards incomplete bodies has been described in some individuals with xenomelia (De Preester, 2013;First, 2005) and third, affected persons frequently pretend in private or public to be amputees. The perception of one's own and another person's body are intimately linked (Schilder, 1935), and sensorimotor processes are influenced by observation and imitation of others (de Guzman et al, 2016;Tsakiris, 2016). Such shared neural mechanisms are modulated by interpersonal relations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Second, a profound admiration for amputees up to a sexual attraction towards incomplete bodies has been described in some individuals with xenomelia (De Preester, 2013;First, 2005) and third, affected persons frequently pretend in private or public to be amputees. The perception of one's own and another person's body are intimately linked (Schilder, 1935), and sensorimotor processes are influenced by observation and imitation of others (de Guzman et al, 2016;Tsakiris, 2016). Such shared neural mechanisms are modulated by interpersonal relations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Besides recognizing the fake model hand as being part of their own body, participants also reported that they felt as if the touch they sensed originated from the location on the rubber hand where they saw the brush touching the rubber hand, rather than from their real hand (Makin, Holmes, & Ehrsson, 2008). Furthermore, recent studies show below rubber hand illusion implicate that the brain is capable of integrating "natural" visual input and direct corticalsomatosensory stimulation to create the multisensory perception that an artificial limb belongs to one's own body (Tsakiris, 2017;Collins et al 2017). …”
Section: Introductionmentioning
confidence: 99%
“…Sense of agency refers to the pre-reflective experience or sense that I am the cause or author of the movement, while sense of ownership is the pre-reflective experience or sense that a limb is part of one's body (Tsakiris, Schuetz-Bosbach, & Gallagher, 2007;Tsakiris, 2017). In normal experience of voluntary or willed action, sense of agency and sense of ownership coincide and are indistinguishable; in the case of involuntary movement, however, it is quite possible to distinguish these two senses (Gallagher, 2000a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cognitive neuroscientists shed an interesting light on the role of a sensory feedback system for the formation not only of a bodily self, but also for the distinction between self and others (Farmer & Tsakiris 2012, Tsakiris 2017. Further insights from cognitive science and developmental psychology suggest that self-consciousness develops in correlation with the development of a theory of mind (e.g., Happé 2003).…”
Section: Introduction To the Special Issue: Investigating The Social mentioning
confidence: 99%